If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -7r = 8 + -9r Solving 10 + -7r = 8 + -9r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '9r' to each side of the equation. 10 + -7r + 9r = 8 + -9r + 9r Combine like terms: -7r + 9r = 2r 10 + 2r = 8 + -9r + 9r Combine like terms: -9r + 9r = 0 10 + 2r = 8 + 0 10 + 2r = 8 Add '-10' to each side of the equation. 10 + -10 + 2r = 8 + -10 Combine like terms: 10 + -10 = 0 0 + 2r = 8 + -10 2r = 8 + -10 Combine like terms: 8 + -10 = -2 2r = -2 Divide each side by '2'. r = -1 Simplifying r = -1
| 2.4k=18.96 | | 4x^2+35x-414= | | 10y-12=48 | | 5(x+6)-7x=26 | | 3w+13=34 | | 7m-10=9m+4 | | 20x-7=3+18 | | .72x+2.4x+32.58=.89x-.55x | | -2t+7=5t | | -3f=-f-10 | | x-8=-2x+3 | | -10u=-9-9u | | -4(x-3)-3x=2(6-3x)-3x | | -6+14+4=32 | | W+(w+2)=-27 | | 10+6z=5z | | 9p-10=10p | | 9-(5a+2)=-a+5 | | 8x^2-6x^2+7x=0 | | -6-3b=-4b | | 4cos^2x=5sinx-2 | | 9-4(4x-3)=3 | | 7x+5x=0 | | 4x^2+8x^2=0 | | 13+d-27=-3 | | 6(3x+6)=-3x-5(1+4x) | | 7/2=1/9x+26/9 | | 4x^2+3x^2-2x=0 | | 2=X+3x^2 | | -3(7n+4)=-2n+26 | | F(19)=4x+7 | | 256=(-4)x |